Analysis of Service Usage Sharia Mobile Banking in The Province of Bengkulu (UNIB Press, 2024)
This research aims to determine the factors that influence the intention to use Islamic mobile banking using the UTAUT (Unified Theory of Acceptance and Use of Technology). This research method uses a quantitative survey approach. The population in this study were all people in Bengkulu Province who used Islamic mobile banking. The sample used in this study was 235 respondents with the data collection method using a questionnaire. Data analysis techniques using structural equation modelling-partial Least Square (SEMPLS) analysis. The results showed that the variables of performance expectancy, effort expectancy and social influence had an effect on customer behavioural intentions in using Islamic mobile banking. In addition, the Trust variable that moderates behaviour intention on actual use also shows a significant effect on behaviour intention. This implies the need for attention from Islamic banking in Bengkulu to continue to develop applications both from benefits and other aspects, so that Islamic banking customers in Bengkulu will continue to increase.